Influence of stereopsis on the ability to perform simulated microsurgery. Issue 4 (April 2020) - Dutton, James; Watkins, Alice; Henderson, Jack; Burgess, Frederick R.; Tint, Naing L.; Dhillon, Baljean; Tatham, Andrew J.
Abstract : A prospective randomized cross-over study showed impaired stereopsis, both total absence and partial impairment, were associated with worse simulated microsurgical performance. Abstract : Purpose: To determine whether impaired or absent stereopsis affects the ability to perform simulated microsurgical tasks. Setting: University of Edinburgh, United Kingdom. Design: Prospective randomized cross-over study. Methods: Visual acuity and stereoacuity were measured. A band-pass filter was placed over the nondominant eye to reduce stereoacuity to 150 seconds of an arc (partial stereopsis), or the nondominant eye was completely occluded (absent stereopsis). Participants completed a computerized surgical simulator task 3 times with a randomized testing order (normal stereopsis, absent stereopsis, and partial stereopsis). The task involved using forceps to grasp and position objects in the anterior chamber. Outcomes included area of ocular injury, time to task completion, and overall score. Results: Ocular damage area was significantly worse with partial stereopsis ( P = .002) and worse still when stereopsis was absent ( P < .001 for normal vs absent stereopsis and P = .005 for partial vs absent stereopsis). The median ocular damage area was 3.55 mm 2 (interquartile range [IQR], 1.21-5.88 mm 2 ) with normal stereopsis, increasing to 6.10 mm 2 (IQR, 3.96-12.47 mm 2 ) with stereopsis reduced to 150 seconds of an arc and to 9.25 mm 2 (IQR, 4.93-18.70 mm 2 ) with no stereopsis. Time taken to complete the task increased and overall score decreased as stereopsis was reduced. The overall score decreased from 53% (IQR, 22.5-82%) under normal stereopsis to 0% (IQR, 0-43.5%) with absent stereopsis. Conclusions: Impaired stereopsis was associated with worse microsurgical performance, which may have implications for surgical training. The absence of stereopsis resulted in worse performance than partial reduction in stereopsis.